Editor’s note - Antić, Ana (Medical Word, 2022)
Dear colleagues and authors, dear readers, Here is the fourth issue of the journal “Medical Word” which represents the collection of abstracts and introductory lectures submitted for the XV Congress of the National Association of Health Workers of Serbia, which was planned and accredited for October 2020, but because of the current epidemiological situation caused by the spread of the COVID-19 pandemic, it has been delayed. In this way, the Editorial Board of the journal expresses their gratitude and support to all health workers who were selfless and worked hard during the entire period of the pandemic. We sincerely hope that the conditions will be agreeable to the planned congress to be held, and for us to exchange the knowledge and experiences that we are transmitting to you in this issue of “Medical Word”. We thank all the authors so far for their work. We also invite interested authors to submit their papers from the medical fields they deal with and also participate in the creation of our journal. In the end, thank you all, dear friends, for reading the journal all this time, noticing our efforts, and supporting us. Until the next issue, Prim. Ana Antić, MD, PhD,Editor-in-chief